Practical Procedures in Elective Orthopaedic Surgery Pelvis and Lower Extremity - Giannoudis, Peter V. (Springer London : Imprint: Springer, 2012)
Practical Procediures in Orthopaedic Surgery covers the most common procedures that a surgeon in training is expected to perform during his residency program for the pelvic ring and the lower extremity. Each procedure has been written by an expert or under a supervision of an expert. Each chapter provides such useful information to the trainee as indications, clinical and radiological assessment, surgical approach, implant positioning, tips and tricks, post-operative complications to be aware of, mode of mobilisation and the time intervals of outpatient follow up. Intra-operative pictures have been incorporated to allow the surgeon to be aware of all the important issues and steps involved for each procedure.